Cuban postage stamp promoting El Mundo Unido Contra La Malaria campaign (1962)
Cuban postage stamp printed to promote world anti-malaria campaign. Depicts a chinchona plant and chemical formulas for chloroquine and primaquine, medications used to treat malaria.
Keywords: Postage stamps; Cinchona; Cuba; Malaria--Treatment; Malaria; Science on postage stamps